Designing Regulatory Institutions for Infrastructure-Lessons from Argentina - Estache, Antonio (World Bank, Washington, DC, 2012)
In 1989, the Argentine government initiated rapid privatization of infrastructure services-mainly gas, telecoms, electricity generation and transmission, and water and electricity distribution in the Buenos Aires metropolitan area. The author reviews the performance of the agencies set up to regulate the privatized utilities against criteria for good design: independence, autonomy, expertise, and accountability. His assessment: the Argentine experience so far shows that the biggest challenges to regulatory design are achieving political independence and introducing rules to ensure accountability.